Influence of the Acetylation Type on the Incidence of Isoniazid-Induced Hepatotoxicity in Patients with Newly Diagnosed Pulmonary Tuberculosis - N. M. Krasnova; N. E. Evdokimova; A. A. Egorova; O. I. Filippova; E. A. Alekseeva; Z. A. Rudykh; Ya. V. Chertovskykh; A. I. Vengerovskii; A. F. Kravchenko; D. A. Sychev (Антибиотики и Химиотерапия)
Introduction. Liver damage can be a dangerous side effect of using isoniazid. Individual susceptibility to isoniazid in humans is dependent on the presence of N-acetyltransferase 2 allelic variants in genome. It was imperative to assess the effect of genetically determined isoniazid acetylation rate in terms of risk of developing isoniazid-induced hepatotoxicity, as well as prevention of potential hepatopathy, and improvement of tuberculosis chemotherapy safety. Aim. To study the effect of acetylation type on the incidence of isoniazid hepatotoxicity in residents of the Sakha Republic (Yakutia) with newly diagnosed pulmonary tuberculosis. Methods. The study included 112 patients with newly diagnosed pulmonary tuberculosis. Genotyping was performed using real-time polymerase chain reaction. The following single nucleotide polymorphisms were studied: rs1801280, rs1799930, rs1799931, rs1799929, rs1208, rs1041983. Hepatotoxicity was determined based on the results of clinical laboratory monitoring and using the criteria developed by the European Association for the Study of the Liver (2019). Results. Hepatotoxic reactions developed more often in slow acetylators (43.2%), compared to fast acetylators (20.7%) and intermediate acetylators (10.9%); p=0.002. Serum alanine aminotransferase activity was 5 or more times above the upper limit of normal activity in 37.8% of slow acetylators, and in 8.7% of intermediate acetylators; p=0.001. Clinical manifestations of isoniazid hepatotoxicity were observed more often in slow acetylators (29.7%), than in fast acetylators (3.4%); p=0.000. Conclusion. Slow acetylation type ought to be considered an important risk factor for developing isoniazid hepatotoxicity in patients with pulmonary tuberculosis.